2007
DOI: 10.1159/000108326
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Grade 2 and 3 Hemorrhoids with Doppler-Guided Hemorrhoidal Artery Ligation

Abstract: Aim: We evaluated the results of the Doppler-guided hemorrhoidal arterial ligation (DG-HAL) method in the management of symptomatic grade 2 and 3 hemorrhoids. Patients and Methods: Between June 2005 and March 2006, 110 consecutive patients with symptomatic grade 2 and 3 hemorrhoids according to the DG-HAL method were treated. All procedures were performed in daycare under spinal anesthesia. The primary objective was the reduction in hemorrhoidal gradation as determined by proctoscopy; the secondary was patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%). This finding is inconsistent with our study, (8,16) because we observed much better outcomes (no failure), but other elements of Ramirez's study and other studies confirmed our results (4,8,10,17,18). Some studies added some modalities such as recto anal repair adjunct to DGHAL with similar results to DGHAL alone (6,16,19 (20).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In a study by Ramirez et al, they also evaluated symptom improvements in patients with grade IV hemorrhoids, who underwent the DGHAL technique and they concluded that most failures occurred in this group (up to 70%). This finding is inconsistent with our study, (8,16) because we observed much better outcomes (no failure), but other elements of Ramirez's study and other studies confirmed our results (4,8,10,17,18). Some studies added some modalities such as recto anal repair adjunct to DGHAL with similar results to DGHAL alone (6,16,19 (20).…”
Section: Discussioncontrasting
confidence: 85%
“…(1,3,4). This technique has been introduced by Morinaga in 1995 23 or Jespersen in 1992, 24 who used a Doppler proctoscope with injected sclerosing agent instead of ligation in the classic Morinaga procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This method, comparable to the elastic band ligations performed blind for several decades, is effective in internal hemorrhoidal disease where there is no prolapse. Several descriptive studies [20][21][22][23][24][25] have reported a shortterm efficacy rate of 90 %, and long-term efficacy of 70-92 %. Post-operative pain was present in 1-6 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…With early success rates of up to 97% [12] and reportedly low complication rates, it seems to be an ideal treatment. Initially, we reported equally good results with a success rate of 85% after an average follow-up of 9 months [10]. Nevertheless, very little is known about its long-term effects and, until now, just 4 studies have shown their results after long-term (>1 year) follow-up [2,5,8,13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rates of effectiveness and patient satisfaction after long-term follow-up are still unknown and, currently, no large, prospective, randomized, controlled trial has been published. We previously published our first experiences and results with DG-HAL [10]. In this article, we describe the long-term follow-up results of this procedure.…”
Section: Introductionmentioning
confidence: 99%